A method for extracting knowledge from medical texts including numerical representation. (11th December 2008) - Kiyoi, Kumiko; Atlam, El-Sayed; Fuketa, Masao; Yoshinari, Tomoko; , Jun-ichi Aoe
In recent years, there has been a tremendous growth of online text information related to digital libraries, medical diagnostic systems, remote education, news sources and electronic commerce. Numeric information is very important to understand numbers in texts of medical opinions. This paper presents a method for determining not only numbers but also expressions of modification to expand the range of corresponding numbers. The meaning of sentences is often determined by the combination of number expressions and their object words. Therefore, the presented method categorises with each meaning of expressions of modification and range expressions. According to experimental results for 948 Computer Tomography (CT) findings, the precision and recall for the extraction of number expressions are 98.23% and 97.62%, respectively. Moreover, the accuracy for the extraction of object words is 90.22%.